EDUKASI GIZI SEIMBANG MENINGKATKAN PENGETAHUAN REMAJA - Khartini Kaluku (PITIMAS: Journal of Community Engagement in Health, 2025)
Changes in dietary patterns among Indonesian communities toward foods high in fat, sugar, and salt have contributed to an increased prevalence of nutritional imbalance, including in Central Maluku. This community service program aimed to improve adolescents’ knowledge of balanced nutrition and healthy lifestyles in Dwiwarna Village. The activity was conducted in February 2025 using a pre-experimental design with a one group pretest–posttest approach. A total of 35 adolescents aged 13–18 years participated in nutrition education sessions involving interactive lectures, group discussions, and the use of printed leaflets. Knowledge was measured before and after the intervention using a structured questionnaire. Descriptive analysis showed an increase in mean knowledge scores from 58% to 90%, representing a 32-percentage-point improvement. Participants demonstrated strong engagement during discussions and showed better understanding of balanced diets utilizing local food sources. The results indicate that community-based nutrition education is effective in enhancing adolescents’ understanding of balanced nutrition. This program supports community-level nutrition improvement and contributes to achieving Sustainable Development Goal (SDG) 2 on food security and nutrition.